Integrating community children’s nursing in urgent and emergency care: a qualitative comparison of two teams in North West England - Kyle, Richard G (BioMed Central, 2012)
BACKGROUND: Despite the policy principle that “children are best cared for at home whenever possible” children continue to have high rates of emergency department (ED) attendance and emergency hospital admission. Community Children’s Nursing Teams (CCNTs) can care for acutely ill children at home but their potential to provide an alternative to ED attendance and hospitalisation depends on effective integration with other services in the urgent care system, such as EDs and Observation and Assessment Units (OAUs). Although challenges of integrating CCNTs have been identified, there has been no comparative assessment of the factors that facilitate or hinder integration of care of acutely ill children by CCNTs with the urgent care system. The aim of this study was to identify enablers and barriers to integration of CCNTs with urgent and emergency care. METHODS: Comparative case studies were conducted of two CCNTs serving Primary Care Trusts in North West England. Twenty-two health professionals including CCNT managers and staff; paediatricians; nurses; children’s ward, ED and OAU staff; commissioners of children’s services; GPs and primary care staff were interviewed between June 2009 and February 2010. Qualitative data were analysed thematically using the Framework approach. RESULTS: Barriers to integration included paediatricians’ perceived lack of ownership of the CCNT, poor communication between consultants and community children’s nurses (CCNs), and weak personal relationships. This prevented early referral to the CCNT as an alternative to hospital care. Enablers of integration included co-location and rotation of CCNs through urgent care settings including OAUs and EDs. This enabled nurses to develop skills, make decisions about referral to home care and gain the confidence of referring clinicians. CONCLUSIONS: Integration of CCNTs at multiple points in the urgent care system is required in order to provide an alternative to inappropriate ED attendances and emergency admission. The principal enablers and barriers are both aspects of normative integration, which involves shared understanding of the contribution of CCNTs and trusting relationships between practitioners. Co-location and rotation of CCNs through acute services can promote integration and appropriate referrals to CCNTs to support families to care for children at home.